Perancangan dan Implementasi Penerangan Jalan Umum Tenaga Surya Berbasis Arus DC untuk Penerangan Kampus Universitas Soerjo Ngawi - Fuzi Marati Sholihah; Rudy Susanto; Henyk Nur Widaryanti (CV. ALIM'SPUBLISHING, 2026)
The design and implementation of a Direct Current (DC)-based Solar-Powered Street Lighting System (PJUTS) represents an alternative solution to improve energy efficiency while promoting the utilization of renewable energy on university campuses. This study aims to design and implement a DC-based solar-powered street lighting system for the campus environment of Soerjo University, Ngawi. The research methodology included field observation, system design, component selection, installation, and performance testing of the proposed system. The implemented system consists of a 20 Wp solar panel, a 12 V 7.5 Ah VRLA battery, a 10 A solar charge controller, and a 20 W DC LED lamp. The solar panel converts solar energy into electrical energy during the daytime, which is stored in the battery and automatically utilized to power the lighting system at night through the controller. The total cost of designing and installing the system was IDR 1,460,000. The results indicate that the system operates effectively and provides adequate illumination for the campus environment according to the planned specifications. System performance is influenced by several technical factors, including installation location, pole height, solar panel tilt angle, cable installation quality, and protection system suitability. Potential problems include short circuits, cable damage, and component performance degradation due to environmental conditions. Therefore, the use of standardized components and regular maintenance is essential to ensure system reliability, efficiency, and service life. This study is expected to contribute to the development of efficient, economical, and environmentally friendly solar-powered street lighting systems, particularly in educational institutions.